RETRACTED: Determinants of Social Commerce Usage and Online Impulse Purchase: Implications for Business and Digital Revolution - Xiang, Huang; Chau, Ka Yin; Iqbal, Wasim; Irfan, Muhammad; Dagar, Vishal (Frontiers in Psychology, 2022)
Since their introduction in the early 2000s, the use of social networking websites has exploded. Many businesses are seeing increased revenue due to their social commerce strategy. Despite the popularity of social commerce websites, some consumers are still hesitant to use them. This study aims to evaluate the factors that influence the adoption of social commerce. A sample of 721 Chinese Wechat users took part in the research. The findings reveal that social capital mediates the positive effect of social commerce adoption and perceived ease of use on techno-stress and online impulse purchasing. Likewise, information overloading mediates the positive effect of social commerce adoption and perceived ease of use on techno-stress and online impulse purchasing. The findings have implications for both practice and research in understanding social commerce adoption in emerging economies.